Bahasa Inggris - wahyunihasa hasan; Laksmyn Kadir; Laode Sultan (Journal of Health, Technology and Science (JHTS), 2021)
This study aims to identify Candida sp in the urine of patients with diabetes mellitus at the Prof. Regional General Hospital. Dr. H Aloe Saboe, Gorntalo City.This type of research is qualitative using descriptive methods and data collection techniques, namely fungal culture examination, interviews and documentation. The sampling technique used in this study was purposive sampling, with a total of 10 people.Based on the results of the study, it was found that Candida albicans, Candida glabrata, Candida parasilopsis, Candida dubliniensis were found in culture media, Candida species were round, smooth, white-cream colored with shiny colonies, and the fungus Aspergilus fumigatus.